Glyceollin I enantiomers distinctly regulate ER-mediated gene expression - Payton Stewart, Florastina (2010)
Glyceollins are pterocarpan phytoalexins elicited in high concentrations when soybeans are stressed. We have previously reported that the three glyceollin isomers (GLY I-III) exhibit antiestrogenic properties, which may have significant biological effects upon human exposure. Of the three isomers, we have recently shown that glyceollin I is the most potent antiestrogen. Natural (-)-glyceollin I recently was synthesized along with its racemate and unnatural (+) enantiomer. In this study, we compared the glyceollin I enantiomers' ER binding affinity, ability to inhibit estrogen responsive element transcriptional (ERE) activity and endogenous gene expression in MCF-7 cells. The results demonstrated similar binding affinities for both ERα and ERβ. Reporter gene assays in MCF-7 cells revealed that while (+)-glyceollin I slightly stimulated ERE transcriptional activity, (-)-glyceollin I decreased activity induced by estrogen. Co-transfection reporter assays performed in HEK 293 cells demonstrated that (+)-glyceollin I increased ERE transcriptional activity of ERα and ERβ with and without estrogen with no antiestrogenic activity observed. Conversely, (-)-glyceollin I decreased the activity of both ER subtypes stimulated by estradiol demonstrating potent antiestrogenic properties. Additionally, each Gly I enantiomer induced unique gene expression profiles in a PCR array panel of genes commonly altered in breast cancer.